Impact of pretransplant asplenia vaccination on anti‐A/B antibody titers in prospective ABO incompatible kidney transplant recipients. Issue 1 (10th January 2023) - Bongetti, Elisa; Sandrin, Mauro S.; Mulley, William R.
Abstract: Background: Asplenia vaccination is employed before ABO‐incompatible (ABOi) transplantation in case splenectomy is needed. Pneumococcal vaccines have been reported, in different patient groups, to increase anti‐A/B titers, through cross‐reactivity to shared polysaccharide epitopes. We investigated the impact of pretransplant asplenia vaccinations on anti‐A/B antibody titers in prospective ABOi renal transplant recipients. Methods: Published asplenia vaccine microbial structures were reviewed to assess expression of A/B antigens. All patients who underwent ABOi transplantation at Monash Medical Centre with anti‐A/B titers taken either side of asplenia vaccination were included in a retrospective cohort study between 2007 and 2021. Patients with paired titers without intervening vaccination were included as controls. Paired titers were compared within groups. Results: A and B antigens were found to be expressed by vaccine specific pneumococcal serotypes. Thirty‐nine ABOi renal transplant recipients received vaccination including at least one pneumococcal vaccine. The most common donor to recipient combination was A1 to O. The median pre‐ and postvaccination anti‐A/B titers were 1:32 and there was no significant change in titers following vaccination (median change in titer 0 dilutions, range –2 to 3, P = 0.43). The same findings were apparent in the control group ( n = 20). There was no significant change in titer by donor blood group or vaccine type. No transplants were canceled or delayed by a rise in anti‐A/B titers postvaccination. Conclusion: Pneumococcal vaccination had no clinically relevant impact on anti‐A/B titers before ABOi transplantation in this cohort. These results provide reassurance regarding the safety of asplenia vaccination before ABOi transplantation. Abstract : Vaccination before transplantation is recommended. Pneumococcal vaccines contain A/B blood group antigens which might increase anti‐A/B titers. Potential ABO incompatible transplant recipients were assessed for a rise in anti‐A/B titers following asplenia vaccination (including against pneumococcus). There was no clinically relevant rise in anti‐A/B titers following vaccination. No transplant was delayed or cancelled due to a rise in titers following vaccination. Key Points: Potential ABO incompatible transplant recipients are encouraged to receive asplenia vaccines including against pneumococci before transplantation. Vaccine specific pneumococcal serotypes share antigenic epitopes with A and B blood group antigens and may theoretically boost antibody titers against blood group antigens. In this study a boosting effect of asplenia vaccination on anti‐A/B titers was not seen in potential transplant recipients. Apslenia vaccination did not delay or prevent transplantation in any of the transplant recipients included in the study and is therefore considered safe before transplantation.